Regulation of Cultivation Temperature on Biomass and Activity of Bifidobacterium breve B2798 - Kailong Liu; Yiting Liu; Zhan Yang; Jie Yu; Guoqiang Yao (Fermentation)
Bifidobacterium is among the dominant flora in the healthy intestine of the human body. It has many probiotic effects such as lowering cholesterol, inhibiting tumors, and regulating immunity. However, fluctuations in culture conditions during cultivation will lead to a decrease in the number of active bacteria. Therefore, more precise control of culture conditions is required to reduce the activity damage caused by environmental fluctuations. Based on this, this study utilized a fully automatic intelligent fermentation tank to develop a cultivation technique suitable for improving the activity and biomass of Bifidobacterium breve B2798. The results show that, under a cultivation temperature of 38.0 °C, the highest viable cell count, which is (2.56 ± 0.04) × 1010 CFU/mL, can be achieved in the culture medium, with the conclusion that the fermentation endpoint should be controlled at the end period of bacteria logarithmic growth when there is the highest viable cell count and bacterial activity in the culture medium. This study has elucidated the influences of different temperatures on the biomass, viable cell count, and activity of Bifidobacterium breve B2798, providing basic data for the later development of industrialized processing techniques for this bacteria strain.